SCHOLARS IN INDIA IN MAMLUK PERIOD AND THEIR RELATIONS WITH RULERS - Dr. Mohammad Alesa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The scholars are the educated part of society, including judges, imams, jurists, teachers, Quran keepers, hadith narrators, and Sufis, and they found great respect in the state and the Mamluk in India from the ruling authority represented by the sultans and rulers, as well as from the public, and it is not possible in any way to consider scholars alone They are a clearly influential part of society, their word is heard and they influence the public more than the ruling authority affects, and accordingly, this research will be to explore the conditions of scholars and their relations with the rulers, as it will address the interest of the people of India in science .